Realist evaluation of Belgian pilot projects for paediatric transmural care: protocol for a mixed methods study - Katrien Vanderwee; Ann Van Hecke; Caroline Verdonck; Kristof Eeckloo; Sara Dequeker; Sabine Van daele; Veerle Duprez; Annemie Charles; Freya Couvin; John Crombez; Lieven De Geyter; Ann De Guchtenaere; et al. (BMJ Open)
Introduction The Belgian healthcare system is to a large extent hospital-centred, prompting government initiatives to shift care towards patient’s homes and reduce hospital stays. To avoid unnecessary hospital stays and offer alternative and innovative forms of care, the Belgian federal health authorities selected five pilot projects for transmural care for chronically ill children. Guided by the Medical Research Council framework, this study aims to evaluate the paediatric transmural care projects to inform new models for paediatric care.Methods and analysis Using a mixed-methods realist evaluation, the study comprises three phases: (1) initial programme theory development, (2) initial programme theory testing and (3) programme theory refinement. In a first phase, the initial programme theory rooted in the normalisation process theory will be refined from insights retrieved from document review and focus group interviews with healthcare professionals. In the second phase, the initial programme theory will be tested using empirical data. Routine data and questionnaires will examine whether characteristics of participants and outcomes are in line with the quintuple aim framework. Focus groups with children, parents and stakeholders, and document analysis will be used to evaluate the structure of the intervention, examine the process and context, and understand more in-depth the outcomes. A budget impact analysis will be used to assess whether the pilot project is affordable. In a third phase, qualitative and quantitative data will be analysed using a convergent mixed-methods model, involving continuous triangulation of multiple data sets to facilitate greater understanding of the context and refinement of the programme theory.Ethics and dissemination The study protocol was reviewed and approved by the Ethics Committee of the Ghent University Hospital (Belgian Registration Number B6702024000193) after consultation with all Ethics Committees of the participating hospitals. Written informed consent will be obtained from participants or their legal representatives prior to data collection. Participant confidentiality will be maintained throughout the study. Study results will be published in international peer-reviewed journals and will be presented at national and international conferences. The general population will be informed of the aggregated results.Trial registration number ClinicalTrials.gov, NCT06679595.